Patient reported outcome measures in breast cancer patients. Issue 7 (July 2018) - Lagendijk, M.; van Egdom, L.S.E.; Richel, C.; van Leeuwen, N.; Verhoef, C.; Lingsma, H.F.; Koppert, L.B.
Abstract: Introduction: In the International Consortium for Health Outcome Measures (ICHOM) breast cancer outcome set Patient Reported Outcome Measurements (PROMs) form an important but rather innovative part. Few data exist on scores per type of breast surgery and how to use scores in surgical practice. We evaluated PROM scores as well as satisfaction with and expectations of the use of PROMs in breast cancer patients using the national and local patient advocate society. Methods: Through an online survey patients were asked to report age, type of breast cancer surgery (whether Breast Conserving Therapy (BCT), mastectomy, autologous or implant breast reconstruction) and time since surgery. PROMs (EORTC-QLQ-C30/BR23 and BREAST-Q postoperative modules) were compared for the different surgeries. Additional comparison was made with literature normative and reference scores. Three questions evaluated satisfaction with PROMs and expectations. Results: 496 patients completed all PROMs and 487 the satisfaction/expectation-questions. Significantly reduced physical functioning was reported following BCT as compared to other surgeries and literature reference values. Satisfaction scores were higher following autologous reconstruction and lower following implant reconstruction as compared to BCT. PRO scores were comparable to normative and references scores except for the 'physical functioning' (BREAST-Q) scores that reported lower in the present study. Ninety-four percent of the participants was (highly) satisfied with future PROM use. Conclusions: Statistical significant differences were found for PROMs following different types of breast surgery. The significance of these results should become clearer trough collection of future data. The great majority of participants considered PROMs as (highly) acceptable and reacted positively on their proposed future use.